Fabrication and characterization of sol-gel derived PZT/WO3 ceramics - T. Sreesattabud (2018)
Lead zirconate titanate/tungsten oxide (PZT/WO3) ceramics were prepared from the powders synthesized by a modified triol sol-gel processing method. In this study, the starting materials used for synthesis of PZT-sol were zirconium (IV) propoxide, titanium (IV) isopropxide, lead (II) acetate trihydrate and 1,1,1,- tris (hydroxymethyl) ethane. To prepare PZT/xWO 3 powders (where x = 0, 0.5, 1 and 3 wt%), nano-sized WO3 was ultrasonically dispersed and mixed with the PZT sol, dried and calcined at 600°C for 4 h. X-ray diffraction results indicated that fully crystallized powders were obtained. Phase characterization suggested that at high WO 3 concentration, the reaction between PZT and WO3 occurred during the calcination process. To prepare PZT/xWO3 ceramics, the powders were pressed and sintered at 1100°C for 6 h. Phase characterization by XRD indicated that the content of WO3 significantly affected tetragonal-to-rhombohedral phase transition. Microstructure of thermally etched samples showed that increasing the content of WO3 decreased grain size of the ceramics. © 2008 Trans Tech Publications, Switzerland.